2012
DOI: 10.1080/00015458.2012.11680853
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Lymphocyte Ratio Predicts Graft Patency Following Lower Limb Revascularisation

Abstract: Post-operative NLR may be a simple, inexpensive means of focussing surveillance resources on patients at high-risk of graft failure. Its value needs to be confirmed in larger cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…This study was the first to show an independent predictive role of high NLR for cardiovascular mortality in both critical limb ischemia and intermittent claudication. In a prospective study of 126 patients with PAOD, who underwent elective or emergency infrainguinal bypass for lower limb revascularization, elevated post-operative NLR was found to be an independent predictor for medium-term graft patency [24]. The prediction of graft failure caused by severe post-operative systemic inflammation had been presented with this study.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…This study was the first to show an independent predictive role of high NLR for cardiovascular mortality in both critical limb ischemia and intermittent claudication. In a prospective study of 126 patients with PAOD, who underwent elective or emergency infrainguinal bypass for lower limb revascularization, elevated post-operative NLR was found to be an independent predictor for medium-term graft patency [24]. The prediction of graft failure caused by severe post-operative systemic inflammation had been presented with this study.…”
Section: Discussionmentioning
confidence: 68%
“…Ergelen et al [10] showed that high NLR value (NLR > 6.97) was associated with increased in-hospital and long-term cardiovascular mortality in patients undergoing primary angioplasty procedures. Moreover, NLR was reported as a strong independent predictor of clinical outcomes including long-term cardiovascular mortality and morbidity after coronary artery bypass grafting [23] and major vascular surgery [24]. The underlying pathophysiology of PAOD is thought to be the mediation of active inflammatory response with neutrophils by numerous biochemical pathways such as releasing of arachidonic acid metabolites and platelet-aggregating factors, cytotoxic oxygen-derived free radicals, and hydrolytic enzymes such as myeloperoxidase, elastase, various hydrolytic enzymes, and acid phosphatases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐one potential papers were included in further review – 16 studies were then excluded: two studies had unclear patient population description with mixture of oncological cases and non‐oncological cases, one study was performed in head and neck cancer patients, four studies were diagnostic in nature, one study had unclear methodology, one study studied had an intermediate outcome, which does not meet the criteria of morbidity, and seven trials were retrospective in nature . Hence, five trials, studying a total of 3487 patients, met all the inclusion criteria (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8 Recently, NLR was reported to be a significant predictor of inflammation and presented as useful in the preoperative diagnosis of acute appendicitis. 9 NLR was found to be significantly higher in patients with acute appendicitis compared with those without acute appendicitis. 8,10,11 NLR was also found to be significantly elevated in patients with complicated appendicitis compared with those with uncomplicated appendicitis.…”
Section: Discussionmentioning
confidence: 78%